Dampak Video Pembelajaran Hari Pahlawan pada Keterampilan Komunikasi Sosial Anak Usia 5-6 Tahun di TKN 001 Bunguran Timur Laut - Renawati Renawati; Resty Desnita; Rusia Yanti; Jenni Afriani; Sahara Wita (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2026)
This study endeavors to elucidate the application of educational videos pertaining to Heroes' Day in fostering the social communication competencies of early childhood learners at Kindergarten 001 Bunguran Timur Laut. Social communication skills are essential for young children as they support language development, social interaction, emotional expression, and the ability to build positive relationships with others. Therefore, educators are encouraged to utilize innovative and engaging learning media that can effectively stimulate children's communication abilities. The methodological framework employed in this investigation was qualitative in nature, utilizing a descriptive approach. The participant cohort comprised 15 children from Group B, aged between 5–6 years. Data were gathered through systematic observation, structured interviews, and comprehensive documentation to obtain a thorough understanding of the learning process and its outcomes. The findings revealed that the integration of educational videos concerning Heroes' Day facilitated the development of social communication skills among children, including verbal expression, responsive inquiry, collaborative engagement, and interactive discourse with peers and educators. The participants demonstrated heightened enthusiasm, greater confidence in expressing their opinions, and increased active participation throughout the instructional sequence. Moreover, the visual and auditory elements of the videos helped children better understand the learning material and encouraged meaningful discussions. Consequently, educational videos pertaining to Heroes' Day may serve as an effective pedagogical medium for nurturing the social communication competencies of early childhood learners at Kindergarten 001 Bunguran Timur Laut.